Mental Health and Wellbeing in Lithuanian Medical Students and Resident Doctors During COVID-19 Pandemic - Stanyte, Agne; Podlipskyte, Aurelija; Milasauskiene, Egle; Király, Orsolya; Demetrovics, Zsolt; Ambrasas, Laurynas; Burkauskas, Julius; Steibliene, Vesta (Frontiers in Psychiatry, 2022)
Background: The Coronavirus disease 2019 (COVID-19) pandemic has had a negative effect on mental health and subjective psychological well-being. One of the most affected populations are medical students, reporting higher levels of depression, anxiety, sleep difficulties and overall poorer well-being. However, the relationship between depression, anxiety, sleep difficulties and subjective psychological well-being have not been extensively researched in medical students in the context of COVID-19 pandemic. The aim of this study was to investigate the associations between depression, anxiety, sleep quality, and subjective psychological well-being. Methods: In sum, 524 medical students and resident doctors (78.6% female, mean age 24±3 years old) participated in an online survey between December 2020 and February 2021. Participants completed the WHO – Five Well-Being Index Questionnaire (WHO-5), the Pittsburgh Sleep Quality Index (PSQ) questionnaire, the Patient Health Questionnaire-9 (PHQ-9), and the Generalized Anxiety Disorder Assessment-7 (GAD-7). Results: Multivariable logistic regression analysis showed that female participants’ worse subjective psychological well-being was associated with sleep difficulties (OR=2.39, 95% CI = 1.37-4.18, p=0.002), higher depression (OR=6.13, 95% CI = 3.46-10.88, p<0.001) and anxiety symptoms (OR=2.95, 95% CI = 1.66-5.22, p<0.001). In male participants, analysis revealed the associations between worse subjective psychological well-being and higher depression scores (OR= 9.94, 95% CI = 3.29-30.03, p<0.001). Conclusions: Sex differences is an important factor to consider when evaluating subjective psychological well-being. Clinicians should be aware of significant contributors, such as sleep patterns anxiety and depression, to subjective psychological well-being.